Phase II Study of Nab-Paclitaxel and Bevacizumab as First-line Therapy for Patients with Unresectable Stage III and IV Melanoma. (February 2015) - Spitler, Lynn E.; Boasberg, Peter; Day, Steven O'; Hamid, Omid; Cruickshank, Scott; Mesko, Shane; Weber, Robert W.
<x xml:space="preserve">Abstract</x> Objectives: This study was an open-label multicenter phase II trial to investigate the efficacy and safety of nab-paclitaxel and bevacizumab as first-line therapy in patients with histologically confirmed unresectable metastatic melanoma. Methods: The treatment regimen consisted of a 28-day cycle in which patients received nab-paclitaxel, 150 mg/m2 through intravenous (IV) infusion weekly for 3 weeks and bevacizumab, 10 mg/kg IV every 2 weeks without a rest period. The 28-day cycle was repeated until there was unacceptable toxicity or disease progression. If 1 drug had to be stopped because of toxicity, treatment was continued with the other drug until disease progression or unacceptable toxicity. The primary endpoint was the progression-free survival rate (PFS) at 4 months. Results: Fifty patients were enrolled. The PFS rate at 4 months was 75%. The median PFS was 7.6 months and the median overall survival was 16.8 months with a median duration follow-up of 41.6 months. The overall survival rate was 64% at 1 year and 30% at 2 years. Ten patients (20%) remain alive. The objective response rate was 36%. Common adverse events associated with this regimen were peripheral neuropathy, fatigue, alopecia, and gastrointestinal disorders. Conclusions: In this phase II multicenter study, this doublet had significant activity in patients with metastatic melanoma, and was well tolerated. These results are promising and follow-up trials to further explore this regimen are warranted.